Review study of Psoriasis in Iraq - Zahraa Sadiq Mzher Sharif; Zahraa Hadi Shukr Hussein; Zahraa Abbas Sharif Dahed; Zahra Hussein Hassan Dhahi (Journal of Medical Genetics and Clinical Biology, 2024)
Abstracts are written in Indonesian and English. Describe the introduction, the purpose of writting, research methods, result and conclusion. Minimum 150 and maximum 250 words.. Psoriasis is a multisystem inflammatory disease with predominantly skin and joint involvement. Beyond the physical dimensions of disease, psoriasis has an extensive emotional and psychosocial effect on patients, affecting social functioning and interpersonal relationships. As a disease of systemic inflammation, psoriasis is associated with multiple comorbidities, including cardiovascular disease and malignancy. The diagnosis is primarily clinical and a skin biopsy is seldom required. Depending on the severity of disease, appropriate treatment can be initiated. For mild to moderate disease, first-line treatment involves topical therapies including corticosteroids, vitamin D3 analogues, and combination products. These topical treatments are efficacious and can be safely initiated and prescribed by primary care physicians. Patients with more severe and refractory symptoms might require further evaluation by a dermatologist for systemic therapy .Psoriasis is a chronic, noncommunicable, painful, disfiguring and disabling disease for which there is no cure and with great negative impact on patients’ quality of life . It can occur at any age. The etiology of psoriasis remains unclear. Psoriasis can also be provoked by external and internal triggers, including mild trauma, sunburn, infections, systemic drugs and stress . Psoriasis involves the skin and nails, and is associated with a number of comorbidities. Skin lesions are localized or generalized, mostly symmetrical, sharply demarcated, red papules and plaques, and usually covered with white or silver scales. Lesions cause itching, stinging and pain. Individuals with psoriasis are reported to be at increased risk of developing other serious clinical conditions such as cardiovascular and other noncommunicable diseases . Psoriasis causes great physical, emotional and social burden . Disfiguration, disability and marked loss of productivity are common challenges for people with psoriasis. Topical and systemic therapies as well as phototherapy are available.